2018
DOI: 10.22454/fammed.2018.158642
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Documentation of Suicidality in a Family Medicine Residency Clinic

Abstract: Background and Objectives: Careful assessment of depression and suicidality are important given their prevalence and consequences for quality of life. Our study evaluated the impact of an educational intervention in a family medicine residency clinic on rates of provider documentation regarding suicidality. Methods: We offered two brief workshops to our clinic staff and created two standardized charting templates to empower and educate providers. One template used with the patient during the clinic visit elici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…This not only signifies a better assessment, practice, and care, but also leads to a less vulnerable psychiatrist in a court of law. Another study reviewed clinical notes and concluded that residents with better quality notes ultimately performed better assessments 40 . Many recommend extemporaneous assessment at the time of discharge, as a discharge summary written even 1 hour after a patient commits suicide, is considered a worthless document.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This not only signifies a better assessment, practice, and care, but also leads to a less vulnerable psychiatrist in a court of law. Another study reviewed clinical notes and concluded that residents with better quality notes ultimately performed better assessments 40 . Many recommend extemporaneous assessment at the time of discharge, as a discharge summary written even 1 hour after a patient commits suicide, is considered a worthless document.…”
Section: Resultsmentioning
confidence: 99%
“…Another study reviewed clinical notes and concluded that residents with better quality notes ultimately performed better assessments. 40 Many recommend extemporaneous assessment at the time of discharge, as a discharge summary written even 1 hour after a patient commits suicide, is considered a worthless document. It is also important to carefully document the thorough process leading to the clinical decision, which helps not only in court cases, but also in the continuity of care.…”
Section: Documentation Of the Suicide Risk Assessmentmentioning
confidence: 99%
“…Training and follow-up reminders regarding adequate documentation of suicide assessment is known to improve quality of documentation. 24 The documentation of the model helps the primary care physician in at least two significant ways. First, it improves patient safety by ensuring all components of the risk assessment are available for future use and accountability.…”
Section: Document: Plan and Rationalementioning
confidence: 99%
“… 13 , 14 Some residencies have risen to this call by implementing trainings and workflow changes, such as workshops and standardized charting templates, finding significant benefit. 15 These studies document helpful interventions to consider when creating and implementing curricula; yet, they are limited in that they solely focus on suicidality and it cannot be concluded that this curricula is beneficial for other types of crises. This study helps fill this critically important literature gap by describing a brief training intervention and point-of-care resources that improved family medicine resident confidence in the outpatient assessment and management of all types of psychiatric crises.…”
Section: Introductionmentioning
confidence: 99%